Self-Efficacy, Goal Orientations, and Religious Moral Orientations on Academic Dishonesty (Jurnal Bimbingan Konseling, 2019)
This study aimed to examine the prediction of self-efficacy, goal orientations, and religious moral orientations on academic dishonesty. The design used in this study was explanatory correlational research design. On the one hand, the samples were gathered through cluster random sampling technique and resulted 275 students. The results showed that: (1) self-efficacy possessed significant influence on academic dishonesty (Î² = -0,141; p < 0.05). (2) Mastery goals and Performance goals influenced academic dishonesty (Î² = -0.21; p < 0.05 and Î² = 0.34; p < 0.05). (3) Religious moral orientations contributed no significant influence on academic dishonesty (Î² = -0,102; p > 0.05). In conclusion, this study gives understanding to counselors regarding the prediction of the involvement of self-efficacy, goal orientations, and religious moral orientations on academic dishonesty.